Best Practice for Historic Claims Staff: The Role of Professional Supervision - Tunupopo, Teagan Martha Marieta (Auckland University of Technology, 2022)
The Historic Claims process of the Ministry of Social Development in Aotearoa New Zealand aims to settle claims from adult survivors who experienced serious abuse whilst in State Care. The Historic Claims staff hear, support and assess the claims of claimants. Their roles involve listening to details of traumatic experiences of physical, mental, emotional, and sexual abuse. The purpose of this research was to explore the role of professional supervision in potentially preventing or mitigating vicarious trauma for Historic Claims staff. This research set out to answer the question of whether Historic Claims staff experience vicarious trauma as part of their professional duties. Additionally, this research explored the role of professional supervision as a support procedure to mitigate against vicarious trauma for Historic Claims staff. A rapid narrative literature review was conducted to determine the potential impacts of consistent staff exposure to sensitive and disturbing historic claims of abuse. This research also investigated whether this impact could be defined as vicarious trauma, the benefits of professional supervision for Historic Claims staff as well as alternative and similar measures to mitigate the harms of vicarious trauma. A total of 86 articles were reviewed for this research with a condensed format that typically summarises the content of each article. Articles were inductively grouped together to present key findings. Key findings included interchangeable definitions and use of vicarious trauma, secondary traumatic stress, and burnout. Findings from this research hypothesised that Historic Claims staff are more likely to experience vicarious trauma due to increased exposure to graphic details of traumatic experiences as reported by claimants. Empathic listening and witnessing claimant distress as they retell their experiences of emotional, mental, physical and/or sexual abuse can also have disturbing and upsetting impacts for Historic Claims staff. Several factors have been identified in this study that mitigate vicarious trauma along with the benefits of professional supervision to include cultural supervision. Implications: The research has important implications for Māori and Pacifica people who are over-represented as claimants. Cultural supervision is an important factor in Aotearoa as well as areas to improve the effectiveness of professional supervision. Māori and Pacific models of trauma and health were also explored in the context of Aotearoa New Zealand. Traditional western focused approaches do not consider well enough Māori and Pacific ideologies of health and the historical context. Cultural competence and context are critical for trauma work, specifically for Historic Claims staff where the majority of claimants identify as Māori and/or Pacific Island descent. More research is needed to explore and protect trauma workers from undergoing psychological trauma that potentially affects client care. Approaches to manage vicarious trauma included debriefing, accepting support from each other, engaging in more energy-fulfilling activities, eating well, staying hydrated and prioritizing sleep hygiene. Measures to guard against vicarious trauma included awareness and education, increasing self-awareness to prevent burnout, organisational support and professional supervision.